2015
DOI: 10.1002/da.22344
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative Evaluation of the Clinical Efficacy of Attention Bias Modification Treatment for Anxiety Disorders

Abstract: The current meta-analysis provides support for ABMT as a novel evidenced-based treatment for anxiety disorders. Overall, ABMT effects are mainly evident when it is delivered in the clinic and when clinical outcome is evaluated by a clinician. More RCTs of ABMT in specific anxiety disorders are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
132
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 36 publications
6
132
1
1
Order By: Relevance
“…AB has been a treatment target in other fields (e.g., anxiety disorders), and AB modification programs have been found to be effective in reducing AB and associated psychopathology (Linetzky, Pergamin-Hight, Pine, & Bar-Haim, 2015) Therefore, further study of AB may contribute to improving existing treatments and to the development of more precise treatments for disorders related to binge eating. Future research directions are discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…AB has been a treatment target in other fields (e.g., anxiety disorders), and AB modification programs have been found to be effective in reducing AB and associated psychopathology (Linetzky, Pergamin-Hight, Pine, & Bar-Haim, 2015) Therefore, further study of AB may contribute to improving existing treatments and to the development of more precise treatments for disorders related to binge eating. Future research directions are discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…Beard et al, 2012; Mogoaşe, et al, 2014). Moreover, active ABMT delivered in clinic settings ameliorates AB and clinician-reported anxiety but not self-reported symptoms in adult anxiety patients (Linetzky et al, 2015). Neuroimaging studies indicate that active training enhanced activation in vlPFC and dlPFC during emotional face processing (Browning et al, 2010; Taylor et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of ABM studies in anxious patients have trained attention away from threat (toward neutral information), invoking an attentional goal state akin to the pattern that conferred risk in our study. Although several studies showed immediate and short-term (e.g., at 4-month follow-up) benefits on anxiety measures (Amir et al, 2009; Schmidt, Richey, Buckner, & Timpano, 2009), more recent findings have been mixed (Linetzky, Pergamin-Hight, Pine, & Bar-Haim, 2015), and no published study has examined clinical effects (depression or anxiety) at longer-term follow-up. In the context of pediatric anxiety, it may be important to consider the possible detrimental effects of training in an avoidance pattern.…”
Section: Discussionmentioning
confidence: 99%